Effects of Chrome Lignosulfonate Concentration and Temperature on Compressive Strength of Cement Class G Used in Oil Well Cementing - Harbi, Jamal (University of Thi-Qar Journal of Science, 2012)
The primary function of Retarders in cement slurry design is to increase the thickening time to allow time for placement of the liquid slurry, The current study to observe the effects of temperature and different concentrations of the substance chrome lignosulfonate used as retarder (one on the additives)to cement class G used in cementing operation wells in oil fields southern Iraq on the compressive strength of the cement .The compressive strength of the samples concrete was measured by UCA equipment with different temperature depending on the depth and internal conditions of the well ( 40C º ,60C ), andpressuring affixed amount of 3000 psi .The experiments showed that the highest compressive strength was 1308 psi ,3130psi,3200psi of cement slurry where the concentration of chrome lignosulfonate 0.1% at temperature 40 C º ,60C º ,80C º respectively after a period of curing time24 hours ,while the less compressivestrength within the study was 326 psi , 412 psi , 477 psi of cement slurry where concentration of chrome lignosulfonate 0.5% after curing time 24 hours. The concrete increased as the temperature during the curing time increased within the range studied and decreasing compressive strength with addition a higher level of chrome lignosulfonate.